The influence of the secondary school-learning examination in mathematics on the studies at the university - Čirba, Stasys; Daunoravičius, Jonas (Lietuvos matematikos rinkinys, 2002)
The dependency of good results of the first year students of the first stage upon the final examination of mathematics taken at school, upon the evaluation mark obtained as well as upon the school location whether secondary school was finished in town or in some country district is discussed. Admitting students to VGTU when counting scores of competition exams 10 scores are added to those who took the state examination in mathematics. The analysis of the studies of the first session having done it was obtained that 13 scores should be added additionally.